Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) and Modernisation of Malay Education, 1917-1957 - Abd Latif, Siti Fathihah; Musa, Mahani (Journal of Al-Tamaddun, 2022)
This article examines the Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) administration of Malay schools in the state of Kelantan from 1917 until the end of British colonial rule in 1957. This involvement is examined through two of its schools, the Maahad Muhammadi (Malay) for boys and Maahad Muhammadi (Malay) for girls. The establishment of MAIK Malay schools is a testament to its professed aims of looking after local welfare, which was not given any attention under British colonial rule. MAIK had faced a myriad of challenges in its administration of Malay schools, whether from within its administration or from outside, especially from Malay schools that were under British control. Based on the qualitative method that involved the perusal of primary documents such as MAIK files, MAIK annual reports, journal Pengasuh and British annual reports on Kelantan from the National Archives of Malaysia and other institutions, this study has found that the British neglect of Malay education has made MAIK indispensable as the organisation responsible for religious affairs and defending local customs in the formal education sector of the state. With this heavy responsibility, MAIK, specifically through its Malay schools, has provided both secular and religious education in schools under its jurisdiction. MAIK’s strategy and improvisations have ensured its schools’ continuity despite competition from the Malay education provided by the colonial government. Through its organisational dynamism, MAIK has enabled itself to be involved in the planning and transformation of primary education in Kelantan from 1917 until 1957.